Glycine receptors and brain development - Avila, Ariel; Nguyen, Laurent; Rigo, Jean-Michel (Frontiers in Cellular Neuroscience, 2013)
Glycine receptors (GlyRs) are ligand-gated chloride ion channels that mediate fast inhibitory neurotransmission in the spinal cord and the brainstem. There, they are mainly involved in motor control and pain perception in the adult. However, these receptors are also expressed in upper regions of the central nervous system, where they participate in different processes including synaptic neurotransmission. Moreover, GlyRs are present since early stages of brain development and might influence this process. Here, we discuss the current state of the art regarding GlyRs during embryonic and postnatal brain development in light of recent findings about the cellular and molecular mechanisms that control brain development.